Penyuluhan inovasi teknologi pemeliharaan ikan Lele Sangkuriang pada kolam terpal lapis hapa dalam pemberdayaan kelompok pintu air di Desa Jampang Kecamatan Kemang Kabupaten Bogor Jawa Barat - Yenni Nuraini; Ade Sunaryo (Unri Conference Series: Community Engagement, 2021)
The implementation of the extension will be successful if the extension worker is able to involve the community in the planning of each extension program. Community empowerment is an effort to meet the desired needs of individuals, groups, and the wider community so that they have the ability to make choices and control their environment in order to fulfill their desires independently. “Pintu Air” Group in Jampang Village, Kemang District, Bogor Regency is one of the groups in which there is an element of community empowerment with catfish farming activities to be able to improve the economy of the community and its members. Fish rearing activities are carried out in tarpaulin ponds by using a filter as a water filter media from the pond so that the air in the outlet channel in the pond can be channeled back to the water reservoir, the use of a filter can reduce dirt and toxins in the tarpaulin pond. With the extension activities carried out, it is hoped that it will have an impact on changing the mindset of the target in the management of cultivation activities carried out in accordance with the potential of local resources and cultivators.